1996
DOI: 10.1007/bf02333405
|View full text |Cite
|
Sign up to set email alerts
|

Academic press and sense of community: Conflict, congruence, and implications for student achievement

Abstract: Abstract. This paper examines tensions between two visions of schooling. One stresses social cohesion (i.e., common beliefs, shared activities, and caring relations between members). The other emphasizes strong academic mission (i.e., values and practices that reinforce high standards for student performance). Though not incongruous, numerous organizational studies reveal the potential for social cohesion and communality to be achieved at the expense of academic demand or "press." To examine their separate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(153 citation statements)
references
References 16 publications
7
142
1
3
Order By: Relevance
“…To create an individuallevel measure for aggregation, we averaged three items, all converted to z-scores: academic achievement (a standard four point grade point average based on self-reported grades in math, science, social studies, and English), educational aspirations (students' ratings, on a scale of 1 to 5, of how much they want to go to college), and enrollment in math and science classes (1 = enrolled in either or both, 0 = enrolled in neither). We refer to the final peer measure-the mean of this individual-level measure for all nominated friends-as friends' academic press because it is akin to measures in the educational literature gauging the emphasis on and pressure for achievement, or academic press, in schools (see Shouse 1996). 1 Adolescent characteristics-To measure potential externalizing responses to academic markers, we calculated Wave I and Wave II versions of four variables and then took the change score (Wave II minus Wave I) for each.…”
Section: Self-perceptions-inmentioning
confidence: 99%
“…To create an individuallevel measure for aggregation, we averaged three items, all converted to z-scores: academic achievement (a standard four point grade point average based on self-reported grades in math, science, social studies, and English), educational aspirations (students' ratings, on a scale of 1 to 5, of how much they want to go to college), and enrollment in math and science classes (1 = enrolled in either or both, 0 = enrolled in neither). We refer to the final peer measure-the mean of this individual-level measure for all nominated friends-as friends' academic press because it is akin to measures in the educational literature gauging the emphasis on and pressure for achievement, or academic press, in schools (see Shouse 1996). 1 Adolescent characteristics-To measure potential externalizing responses to academic markers, we calculated Wave I and Wave II versions of four variables and then took the change score (Wave II minus Wave I) for each.…”
Section: Self-perceptions-inmentioning
confidence: 99%
“…In brief, research (Resnick et al, 1997;Verdugo & Schneider, 1999;Gottfredson, 2001;Shouse, 1996) shows that by providing the core elements for safe and supportive learning environments, academic motivation and achievement are likely outcomes. Research on safe and supportive learning environments (Newmann & Wehlage, 1995;Stigler & Heibert, 1999;Ragland et al, 1999) also shows that increased student learning is obtained when the entire school community embraces collective responsibility for developing and meeting educational goals.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous research in the sense of community literature has determined that sense of community does have an influence on academic success (Shouse, 1996;Sherblom, et aI., 2005;Israel, et aI., 2001), Sanchez, et aI., 2006). However, this study did not find that sense of community influences GPA.…”
Section: Comparing the Findings With Published Literaturementioning
confidence: 99%
“…Shouse (1996) showed that schools that have a high sense of community have an increased academic achievement. In this study, the researcher looked at schools that have high shared values, a common agenda of activities, and an ethic of caring and collegiality.…”
Section: Sense Of Community and Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation